The Motivation of Learning English: A Descriptive Case Study of Indonesian Lecturers - Noprival (Universitas Cokroaminoto Palopo, 2022)
Although many scholars have conducted studies on the motivation of learning, little scholarly work reports the motives of lecturers learning English; the participants of previous studies are predominantly students. Further, a majority of those previous studies have been conducted using exclusively quantitative methods. To address these empirical and methodological gaps, the current research employed a qualitative descriptive case study method to examine the Indonesian lecturer motivation for learning English. This study utilised in-depth interviews to gather information from participants. The thematic analysis of the semi-structured interviews presented that the lecturers’ motivation for learning English were engaging in international scientific meetings, teaching, writing a research article, reading literature, and preparing a doctoral program. The findings revealed that instrumental motivation dominated Indonesian lecturers to improve their English. The implication of this study is that any language learners adopt or adapt the motivations from the participants of this study and succeed in learning English.